2021
DOI: 10.1364/boe.434789
|View full text |Cite
|
Sign up to set email alerts
|

In vivo harmonic generation microscopy for monitoring the height of basal keratinocytes in solar lentigines after laser depigmentation treatment

Abstract: The development of solar lentigines (SLs) is related to chronic ultraviolet exposure-induced cell senescence. We have previously demonstrated that basal keratinocyte enlargement is a morphological hallmark of skin senescence correlated to the process of skin aging, while clinical studies on the long-term monitoring of the cellular morphological changes in SLs after laser treatment are lacking. In this study, we have developed the harmonic generation microscopy (HGM) for in vivo monitoring the height of basal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A Cr:forsterite-based HGM system [23][24][25][26][27]32 with a central wavelength of ~1260 nm was used for skin imaging. A 1.15 numerical aperture objective (×40; working distance 250 μm; UApo N 340; Olympus) was used to focus the laser beam on the skin to capture high-resolution images.…”
Section: Hgmmentioning
confidence: 99%
See 2 more Smart Citations
“…A Cr:forsterite-based HGM system [23][24][25][26][27]32 with a central wavelength of ~1260 nm was used for skin imaging. A 1.15 numerical aperture objective (×40; working distance 250 μm; UApo N 340; Olympus) was used to focus the laser beam on the skin to capture high-resolution images.…”
Section: Hgmmentioning
confidence: 99%
“…Previous studies have shown that combining a ~1260 nm harmonic generation microscopy (HGM) system with second harmonic generation (SHG) and third harmonic generation (THG) modalities can provide a label-free, noninvasive optical virtual skin biopsy with a resolution of 0.4 mm and a penetration depth of 270 mm to observe the epidermis and papillary dermis. [23][24][25][26][27] The image of HGM system is dichromatic and consists of two signals, THG and SHG, respectively. THG signal mainly comes from the components and structures of epidermis, such as melanin pigment, multilayer structures, organelles, and lipids, while SHG mainly comes from the contrast of type I collagen fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imaging plane was moved to different depths by tuning the 3D stage along the optical axis. Following a similar pulse width measurement and dispersion control [69], the pulse width after the objective was estimated to be 28 fs. The epi-THG transverse and axial resolutions were approximately 0.4 and 1.1 μm, respectively [70].…”
Section: Tightly-focused Epi-thg Microscopy (Tfetm)mentioning
confidence: 99%
“…Furthermore, longitudinal IVM may be used to monitor response to various therapies without biopsy, such as endoscopic mucosal or radiofrequency (RF) ablation, photodynamic therapy, skin pigmentation disorder treatments, and others. 34 37 …”
Section: Introductionmentioning
confidence: 99%